Integrarea ştiinţei şi învăţământului superior în contextul Procesului de la Bologna [Articol] - Rusnac, Gheorghe; Guțu, Vladimir (CEP USM, 2007)
The article is dedicated to the problem of integration of science and higher education on the level of Bologna Process. There are reflected the tendencies on the European and national planes, the relation between teaching-studding researching, is being discussed in higher education. Special attention is paid to doctoral education.
Keywords: Proces de la Bologna; învăţământului superior